Pengaruh Pembelajaran PKn terhadap Wawasan Kebangsaan Mahasiswa Universitas Riau - Verli Novaroza; Hambali Hambali; Hariyanti Hariyanti; Mirza Hardian (Journal on Education, 2023)
This study aims to determine the effect of Civics learning on the national insight of Riau University students. This research was conducted at the University of Riau with a total of 100 respondents. This research is motivated by the existence of several problems with nationalism at the University of Riau such as there are still students who are not familiar with Pancasila as the state ideology, there are still students who participate in inter-faculty disputes and a weakening sense of defending the country. The study used a quantitative approach, this approach was chosen to determine the effect of Civics learning on the national insights of Riau University students. In this study, the results were obtained using the Simple Linear Regression Test, F Test and R Test. very good. in the Learning variable 96.17% where the range is at 75.01% - 100%. It can be concluded that Civics learning is at a very good level. While the National Insight of Riau University students is at a very good level of 97.05% where the range is at 75.01% - 100%. It can be concluded that students' national insight is at a very good level.